Evaluation of an Integrated Programme of Physical Exericesa with Nursey-aged Children: Impact on Motor Achievements - Petrić, Vilko; Kostadin, Lucija; Peić, Mirela (Revija za elementarno izobraževanje, 2018)
The aim was to determine if there is a possibility of conducting an integrated programme of physical exercise with nursery-aged children, as well as to evaluate its impact on their motor achievement. The sample consisted of nursery-aged children. The sample of variables comprises four tests for evaluating motor achievement based on the various movement structures that allow mastery of space, obstacles and resistance, as well as the manipulation of objects. The differences between the experimental and control groups were tested with Student’s t-test. The results show that these programmes yielded exceptional results with regard to motor achievement.DOI: 10.18690/rei.11.3.189 -200.2018COBISS-ID:
Keywords: children of an early age; integrated programme of physical exercise; comprehensive motor development